Pengaruh Stres Kerja dan Motivasi Kerja terhadap Produktivitas Karyawan PT. Kencana Sawit Indonesia Cabang Solok Selatan - Elvi Nilda (Fakultas Syariah IAIN Kerinci, 2025)
This study aims to analyze the effect of work stress and work motivation on employee productivity at PT. Kencana Sawit Indonesia. The study employed a quantitative approach with a causal survey design. The research population consisted of all permanent employees, and the samples were selected using a purposive sampling technique totaling (unknown) respondents. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression through SPSS software. The results showed that work stress had a significant negative effect on employee productivity, while work motivation had a significant positive effect on productivity. Simultaneously, work stress and work motivation significantly affected employee productivity. These findings emphasize the importance of stress management and the enhancement of work motivation in supporting employee productivity within the palm oil plantation work environment.